A arte dos códigos secretos em sala de aula: explorando conceitos de matemática básica em criptografia - Medeiros, Willa da Silva (2020)
Teaching mathematics is not an easy task, since it has long been considered, among the vast majority of students, to be a subject full of rules and formulas that seem to have no important practical application. In this sense, it is crucial to constantly explore the applications of mathematical content in students’ daily life. For this purpose, the present work seeks, from cryptography, to explore the relationship between some basic mathematics themes and cryptographic methods. The main goals are: to broach some important historical facts concerning the development of secret codes and cryptography in general; to relate basic arithmetic to a type of cryptography that is very important for Internet security today, RSA cryptography; to emphasize how certain concepts of mathematics can be present in the study of cryptography developed here and how it can be useful for student learning. This work reveals the importance of dealing with subjects of this nature in mathematics classes. At a time when the Internet has become indispensable for human beings, it is necessary for people from an early age to know at least the most basic notions of the intelligence responsible for all the security of this communication vehicle, cryptography. Besides, it is extremely important to show students the role of mathematics in the efficiency and development of this science. Thus, some algorithms (guides) were produced that serve to support the teacher to introduce and explore cryptography as an application of mathematics in the classroom